Real-Time OS 기반의 로봇 매니퓰레이터 동력학 제어기의 구현 및 성능평가 - 高在源(Jaw-Won Kho); 林東哲(Dong-Cheol Lim) (전기학회 논문지 P권, 57(2), 2008)
In this paper, a dynamic learning controller for robot manipulator is implemented using real-time operating system with capabilities of multitasking, intertask communication and synchronization, event-driven, priority-driven scheduling, real-time clock control, etc. The controller hardware system with VME bus and related devices is developed and applied to implement a dynamic learning control scheme for robot manipulator. Real-time performance of the proposed dynamic learning controller is tested and evaluated for tracking of the desired trajectory and compared with the conventional servo controller.